2016
DOI: 10.1007/s11099-016-0185-y
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a fluorescence analysis of high-yield rice (Oryza sativa L.) LYPJ during leaf senescence

Abstract: Photosystem II (PSII) photochemistry was examined by chlorophyll (Chl) a fluorescence analysis in high-yield rice LYPJ flag leaves during senescence. Parameters deduced from the JIP-test showed that inhibition of the donor side of PSII was greater than that of the acceptor side in hybrid rice LYPJ. The natural senescence process was accompanied by the increased inactivation of oxygen-evolving complex (OEC) and a lower total number of active reaction centers per absorption. It indicated that the inhibition of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Similarly, a large seasonal variation in the fluorescence transient, with an apparent effect on the area above the fluorescence curve (indicated by the parameter AREA) has been found in cereal crop species [66]. In some other parameters (e.g., F v /F m and V k /V J ), developmental variation was found only under conditions of severe leaf senescence [67]. We could only guess that there were coincidences in the minor factors (e.g., microclimate, soil temperature, and so on) which led to the slightly faster development of new leaves in one of the blocks in early spring, which was then detected by the sensitive fluorescence parameters (i.e., RC/ABS and AREA) during the early spring measurements.…”
Section: Of 15mentioning
confidence: 77%
“…Similarly, a large seasonal variation in the fluorescence transient, with an apparent effect on the area above the fluorescence curve (indicated by the parameter AREA) has been found in cereal crop species [66]. In some other parameters (e.g., F v /F m and V k /V J ), developmental variation was found only under conditions of severe leaf senescence [67]. We could only guess that there were coincidences in the minor factors (e.g., microclimate, soil temperature, and so on) which led to the slightly faster development of new leaves in one of the blocks in early spring, which was then detected by the sensitive fluorescence parameters (i.e., RC/ABS and AREA) during the early spring measurements.…”
Section: Of 15mentioning
confidence: 77%
“…Nonetheless, the increase of V K /V J , also known as W K , revealed OEC inactivation [ 19 ]. For instance, it was observed under water stress [ 20 ], salt stress [ 18 , 25 ], low-nitrogen fertilization [ 31 ], or during leaf senescence [ 49 ]. Along the experiment, the increase occurred in S120 plants ( Figure 2 a), while as expected, V K /V J remained proximal to 0.5 in the control plants [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the protection mechanism arose at the expense of useful trapping and thus at the expense of energy delivery into the electron transport chain per excited cross section (ETo/CS M ) ( Figure 6 ). Reduction of ETo/CS M also happened in salt-stressed sweet sorghum [ 25 ] and wheat [ 48 ], drought- or heat-stressed wheat [ 66 ], and senescing flag leaves of rice [ 49 ]. Increased heat dissipation and higher number of RC silent resulted in lower electron transport flux per cross section in a less than a more salt-stress tolerant barley landrace [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that supplemental irrigation and N application decreased W k and V j values, and increased Ψ o values. The W k values represent the damage to oxygen-evolving complexes (OEC), while V j and Ψ o represent changes in the acceptor side of photosystem (PSII; Wang et al 2016). The current results indicated that supplemental irrigation and N application reduced OEC damage, and improved the electron transfer capability of both the donor and the acceptor sides at the PSII reaction centre.…”
Section: Discussionmentioning
confidence: 99%
“…The current results indicated that supplemental irrigation and N application reduced OEC damage, and improved the electron transfer capability of both the donor and the acceptor sides at the PSII reaction centre. Additionally, PI abs is more sensitive to environmental stress and has been used to study the responses of the plant to abiotic stresses including natural senescence (Wang et al 2016). Results showed that plants from the rainfed and no N application treatments had lower PI abs values, compared with the supplemental irrigation and N application treatments.…”
Section: Discussionmentioning
confidence: 99%